2012
DOI: 10.1292/jvms.11-0057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Factors during Superovulation on Embryo Production in Korean Holstein Cattle

Abstract: ABSTRACT. The aim of this study was to investigate the influence of key parameters (donor parity, milk production, post-parturient day, season and milk recording data) associated with efficiency of embryo recovery (ER) in Holstein cattle. Elite Holstein cows and heifers were selected for ER, while Holstein heifers were used as recipients. The numbers of transferable embryos (TEs) produced were not significantly different when analyzed in terms of donor parity, milk production, postparturient day and season. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
10
1
7
Order By: Relevance
“…Maximal TNO and NTE occurred during the spring season, which is inconsistent with a previous finding (Lee et al, 2012) that NTE is highest during the fall. However, Lerner et al (1986) have reported that season has no significant effects on NTE.…”
Section: Discussioncontrasting
confidence: 99%
“…Maximal TNO and NTE occurred during the spring season, which is inconsistent with a previous finding (Lee et al, 2012) that NTE is highest during the fall. However, Lerner et al (1986) have reported that season has no significant effects on NTE.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have recognized metals as a threat to sea turtles; however, Cr levels in sea turtles have only been reported in two studies. One study found low levels of Cr in blood plasma of hawksbill sea turtles (Suzuki et al, 2012). This outcome is not surprising as in humans and other terrestrial animals blood plasma levels are low (ATSDR 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Only two of these studies measured Cr. One study reported low Cr levels (0.039 μg/ml) in the plasma of captive hawksbills (Suzuki et al, 2012). The other reported average Cr levels from 12 stranded loggerhead turtles in the Mediterranean of 1.05, 1.57, and 1.43 mg/kg dry weight in liver, kidney and muscle, respectively, with the highest levels found in lung tissue (2.29 mg/kg) (Storelli et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the increasing parity did not affect the embryo recovery (ER) or transferable embryo (TE) content (Donaldson, 1984;Lerner et al, 1986;Hasler, 1992), although a large-scale parity order analysis could not be undertaken in Korea (Lee et al, 2012). However, Gebeyehu (2007) found that the parity order was significantly higher (P < 0.01) for days open and the calving interval.…”
Section: Effect Of the Parity Ordermentioning
confidence: 99%